GE_GERICHTE P/19427/2019 vom 10. März 2021 - GE Cour de justice (2021)
SÉQUESTRE(MESURE PROVISIONNELLE);AVOIRS BANCAIRES;PROCÉDURE DE FAILLITE;CESSION DE CRÉANCE(LP) | CPP.263.al1; CP.71.al3; CP.70.al2